The Mechanisms of Cucurbitacin E as a Neuroprotective and Memory-Enhancing Agent in a Cerebral Hypoperfusion Rat Model: Attenuation of Oxidative Stress, Inflammation, and Excitotoxicity - Liu, Zhiyong; Kumar, Manish; Devi, Sushma; Kabra, Atul (Frontiers in Pharmacology, 2021)
Impaired cerebral hemodynamic autoregulation, vasoconstriction, cardiovascular and metabolic dysfunctions cause cerebral hypoperfusion (CH) that triggers pro-oxidative and inflammatory events. The sequences linked to ion-channelopathies, calcium and glutamatergic excitotoxicity mechanisms ensue widespread brain damage and neurobehavioral deficits including memory, neurological, and sensorimotor functions. The vasodilatory, anti-inflammatory, and anti-oxidant activities of cucurbitacin E (CuE) can alleviate CH-induced neurobehavioral impairments. In the present study, neuroprotective effects of CuE were explored in rat model of CH. Wistar rats were subjected to permanent bilateral common carotid artery occlusion to induce CH on day 1 and administered CuE (0.25, 0.5 mg/kg) and/or Bay-K8644 (calcium agonist, 0.5 mg/kg) for 28 days. CH caused impairment of neurological, sensorimotor, and memory functions that were ameliorated by CuE. CuE attenuated CH triggered lipid peroxidation, 8-hydroxy-2′-deoxyguanosine, protein carbonyls, tumor necrosis factor-α, nuclear factor-kappaB, myeloperoxidase activity, inducible nitric oxide synthase, and matrix metalloproteinase-9 levels in brain ensuing decrease in cell death biomarkers (lactate dehydrogenase and caspase-3). CuE decreased acetylcholinesterase activity, glutamate, and increased γ-aminobutyric acid levels in brain. An increase in brain antioxidants was observed in CuE treated rats subjected to CH. CuE has potential to alleviate pathogenesis of CH and protect neurological, sensorimotor, and memory functions against CH.